Talent Management for Digitized and Sustainability-Oriented Supply Chains in Traditional Manufacturing Firms - Miśkiewicz, Mateusz (Digital Repository of Theses, 2026)
This dissertation explores how Talent Management (TM) acts as a strategic enabler of Digital Transformation (DT) and Sustainability (SUS) within traditional manufacturing small and medium-sized enterprises (SMEs). By integrating perspectives from human resource management, organizational change, and operations strategy, this research develops a Human-Centered Transformation Framework (HCTF) that explains how SMEs can align people, technology, and purpose to achieve long-term competitiveness and resilience. A mixed-method approach—combining quantitative survey data with qualitative interviews—was employed to investigate the relationship between TM, DT, and SUS in the context of the European manufacturing sector. The findings reveal that while technology and sustainability represent the technical and ethical dimensions of transformation, the human factor—through leadership, culture, and continuous learning—serves as the critical link enabling integration. The study contributes to theory by merging fragmented research streams on digitalization, sustainability, and talent management into one unified model. Practically, it provides actionable insights for SME leaders and policymakers seeking to manage the “twin transitions” of Industry 4.0 and the European Green Deal. The dissertation concludes that technology enables change, but people make transformation happen. Keywords: Talent Management, Digital Transformation, Sustainability, SMEs, Leadership, Organizational Culture, Industry 4.0, Human-Centered Transformation